The Effectiveness of Entomopathogenic Bacillus thuringiensis on Rice (Oryza sativa) in Muara Enim Regency, South Sumatera Indonesia - Ririn, Nurbandini; Yulia , Pujiastuti; Chandra , Irsan (BIOVALENTIA: Biological Research Journal, 2025)
Insecticide spraying in rice ecosystems not only significantly reduces pest insect populations but also populations of predatory arthropods, parasitoids and neutral insects. Therefore, other alternatives are needed that are safer for the environment, non-target organisms and humans. One alternative with biological agents using Bacillus thuringiensis bacteria that are entomopathogenic. The aim of the research was to study the effect og Bacillus thuringiensis towards population of rice pests, predatory arthropods and natural enemies. The research was conducted in Muara Enim Regency from July to October 2023. Observations of agronomic traits of rice  in the form of plant height, number of rice tillers and production yield. Insect observations using pitfall trap insect nets and visual. This study used a completely randomized design (CRD) with 3 treatments consisting of B. thuringiensis bioinsecticide treatment, synthetic insecticide made from abamectin and control repeated 6 times every 2 weeks. The results showed the application of B. thuringiensis bioinsecticide had an effect on plant height, number of rice tillers and production yield. In observations using pitfall traps and insect nets, the highest number of species was obtained from the Coleoptera and Hemiptera orders and had a Shanon-Winner diversity index value (H') in the application of Bioinsecticide B. thuringiensis 3.31 Synthetic insecticide 2.51 and control 3.11.  In general, B. thuringiensis could be used as an alterbative insecticide to control insect pest but it was safe for natural enemies and pollinator